Amanah Saham Nasional Berhad (ASNB): Butterworth / Amira Afiqah Mat Rosli - Mat Rosli, Amira Afiqah (Universiti teknologi MARA,Perlis, 2023)
Amanah Saham Nasional Berhad (ASNB) has been active in the unit trust market for 44 years as of 2023. Due to the fact that this business is one of the most reputable and trusted businesses in Malaysia, the vast majority of customers do not need to be concerned about a lack of trust. Additionally, ASNB has managed unit trusts for many years. During the 24 weeks I spent receiving industrial training at Amanah Saham Nasional Berhad Butterworth, I learned a lot of fresh information that I may utilise when I begin working. After taking part in this internship programme, students' learning becomes more realistic and clearly quantifiable in terms of their accomplishments and success in a particular position. As an intern, I was given hands-on experience with customer service and administration, as well as rigorous attention to skills in communication, digital skills, teamwork and stress resistance. This report will provide a brief overview of the background, accomplishments, and range of products and services offered by ASNB. Additionally, this report will display the findings for the dependent and independent variables of The Determinant of Profitablility: Commercial Bank in Malaysia. The aim of this paper is to investigate the factors that influence commercial banks' profitability in Malaysia. Four distinct characteristics that were examined for their connections to profitability are the foundation of this investigation. These elements are the bank's size (SIZE), return on assets (ROA), capital ratio (CAP), liquidity risk (LIQ), and (SIZE). Data for this study was gathered from ten commercial banks and spans the years 2011 through 2020. (10 years). The research approach employed in this study is the Static Panel Data Analysis model, and the data were taken from Refinitv Eikon Datastream in Microsoft Excel. It is shown through the use of fixed effects regression that ROA and SIZE have a significant influence on the profitability of Malaysia's commercial banks. However, the CAP and LIQ show a poor correlation with profitability.